Analisis Strategi Bersaing Home Industri Kasur Lantai Dengan Menggunakan Strategi Generik Porter Dan SWOT (Study Home Industri Kasur Lantai di Sukorejo Pasuruan) - Lutfi Lutfi (Universitas Yudharta Pasuruan, 2022)
The research study in this journal to analyze the business strategy of the Floor Mattress Home Industry based on a competitive strategy using Porter's generic analysis and by using SWOT analysis. This type of research uses descriptive qualitative. The research sample used a purposive sampling technique. Data analysis techniques used data analysis from various sources as a whole, data reduction, and SWOT analysis. The results showed that with Porter's generic business strategies that can be developed in the home Floor Mattress Industry include a low-cost strategy, namely by reducing production costs to a minimum so that selling prices are low, the second is product differentiation Floor mattresses that are developed especially differentiation in product quality and the third a narrower market segmentation focus on middle to lower consumers, sales are made to traditional markets and small-scale shophouses. Based on the SWOT analysis, namely IFAS, EFAS and the SWOT matrix, the strategy for developing the Floor Mattress Home Industry in Sukorejo Pasuruan sub-district is to create a distinctive feature or differentiator from other floor mattress businesses using the S and T strategies